Beta-endorphin suppresses release of thyrotropin-releasing hormone in rat hypothalamus during acute hypoxia exposure. - HOU Tian-De; DU Ji-Zeng (Acta Pharmacologica Sinica, 2016)
AIM: To study the influences of beta-endorphin (beta-EP) on the responses of thyrotropin-releasing hormone (TRH) in median eminence (ME) and paraventricular nucleus (PVN) of hypothalamus to acute hypoxia in conscious rats. METHODS: Brain TRH, serum T3 and T4 were measured by radioimmunoassay. The male Wistar rats were exposed in a simulated hypobaric chamber at 7000 m altitude (8.2 % O2) for 2 h. beta-EP was given by intraventricular injection (icv) before hypoxia. RESULTS: beta-EP (0.1 or 1 micromol/L, icv) elevated TRH levels of ME by 12 % (P